1996
DOI: 10.1007/bf02282835
|View full text |Cite
|
Sign up to set email alerts
|

Growth curves in untreated Ullrich-Turner syndrome: French reference standards 1-22 years

Abstract: Reference curves for untreated Ullrich-Turner syndrome are provided, which should form a basis for assessing the impact of growth-promoting treatment in this disorder.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

1997
1997
2016
2016

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(18 citation statements)
references
References 15 publications
1
17
0
Order By: Relevance
“…Although NF1 is a frequent genetic disorder and many NF1 clinics are specifically devoted to it, no data on auxological patterns of NF1 subjects are presently available, whereas growth charts for clinical use have been traced for less frequent diseases like achondroplasia [Horton et al, 1978], hypochondroplasia [Appan et al, 1990], Williams syndrome [Morris et al, 1988], Rubinstein-Taybi syndrome , and Ullrich-Turner syndrome [Bernasconi et al, 1994;Sempé et al, 1996]. Actually, when growth disturbances are part of a disease, disease-specific growth charts are useful to define the main differences in the growth profile from the healthy population to understand the pathogenesis of the condition and to make the occurrence of a secondary growth disorder clearly detectable [Ranke, 1989].…”
Section: Discussionmentioning
confidence: 99%
“…Although NF1 is a frequent genetic disorder and many NF1 clinics are specifically devoted to it, no data on auxological patterns of NF1 subjects are presently available, whereas growth charts for clinical use have been traced for less frequent diseases like achondroplasia [Horton et al, 1978], hypochondroplasia [Appan et al, 1990], Williams syndrome [Morris et al, 1988], Rubinstein-Taybi syndrome , and Ullrich-Turner syndrome [Bernasconi et al, 1994;Sempé et al, 1996]. Actually, when growth disturbances are part of a disease, disease-specific growth charts are useful to define the main differences in the growth profile from the healthy population to understand the pathogenesis of the condition and to make the occurrence of a secondary growth disorder clearly detectable [Ranke, 1989].…”
Section: Discussionmentioning
confidence: 99%
“…Birth measurements and postnatal height are expressed as SDS for GA and chronological age, respectively, based on the normative data for the general population at birth (32) and, thereafter, for the general (33) and TS populations (12). SGA was defined as a BL or weight of K2 SDS or less.…”
Section: Methodsmentioning
confidence: 99%
“…In a French study of 160 patients, 45% of patients were found to have been small for gestational age (SGA), for length and/or weight (11). Height velocity decreases during childhood and the height deficit increases during adolescence due to the absence of a pubertal growth spurt, resulting in a spontaneous adult height (AH) approximately 20 cm shorter than mid-parental height (143 cm in France) (11,12). Most clinical trials have shown that treatment with recombinant human growth hormone (GH) can yield a mean height gain of about 7 cm, varying with age at treatment initiation and treatment duration (13,14).…”
Section: Introductionmentioning
confidence: 99%
“…Growth charts have been developed for a number of other special populations of infants and children. These have included Down syndrome (Al Husain, 2003;Cremers et al, 1996;Cronk et al, 1988;Cronk, 1978;Myrelid et al, 2002;Piro et al, 1990;Toledo et al, 1999), neurofibromatosis (Szudek et al, 2000), Ullrich-Turner syndrome (Isojima et al, 2009;Sempe et al, 1996), pediatric liver transplant recipients (Saito et al, 2007), Laron syndrome (Laron et al, 1993), Noonan syndrome (Witt et al, 1986), and achondroplasia (Horton et al, 1978). In the future, if measurements tracked in such charts can be linked to health outcomes (e.g., mortality) the charts will be more valuable to clinicians.…”
Section: Applications To Other Areas Of Health and Diseasementioning
confidence: 96%